Shakespeare as a challenge for literary biography : a history of biographies of Shakespeare since 1898 - Maltby, Arthur (Edwin Mellen Press, 2009)
This book argues that, despite the quantity of writing and record searching, Shakespearean biographies remain curiously unsatisfactory, even contradictory.